2021
DOI: 10.1002/csr.2173
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility perceptions and sustainable safety behaviors among frontline employees: The mediating roles of organization‐based self‐esteem and work engagement

Abstract: This study aimed to examine the relationship between perceptions of corporate social responsibility (CSR) and sustainable safety behaviors among frontline employees. Drawing on social identity and social exchange theories, this study hypothesized that frontline employees' organization‐based self‐esteem (OBSE) and work engagement mediate the relationship between CSR perceptions and sustainable safety behaviors. Using data collected from 222 flight attendants in South Korea, structural equation modeling was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…The path analysis also shows that SP has a positive and significant effect on SA and, therefore, hypothesis H5 is accepted. In this respect, this study's findings are consistent with those of previous studies [9,24,52,54,55]. Aramco organizes its health and safety policies along with other HR policies to affirm the company's commitment to the well-being of its frontline workers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The path analysis also shows that SP has a positive and significant effect on SA and, therefore, hypothesis H5 is accepted. In this respect, this study's findings are consistent with those of previous studies [9,24,52,54,55]. Aramco organizes its health and safety policies along with other HR policies to affirm the company's commitment to the well-being of its frontline workers.…”
Section: Discussionsupporting
confidence: 90%
“…Among South Korean frontline employees, there is a positive correlation between Corporate Social Responsibility (CSR) and frontline workers' sustainable safety behaviors. Moreover, the SP creates entirely the frontline workers' SA [55]. Consequently, an effective SP is a powerful instrument to save frontline workers' lives and to make them accountable for adopting such policies in their workplaces.…”
Section: Safety Policy (Sp) and Safety Accountability (Sa)mentioning
confidence: 99%
“…Furthermore, prior studies demonstrated that employee perceptions of CSR practices as substantive (i.e., genuine and other-serving) were positively associated with increased work meaningfulness (Donia et al, 2019) and psychological safety (Ahmad et al, 2019). In addition, working for a socially responsible enterprise can raise employees' OBSE (Hur et al, 2022). Therefore, according to Kahn's (1990) model, we believe that employees' substantive CSR attributions will give rise to the three psychological antecedents of engagement.…”
Section: Introductionmentioning
confidence: 80%
“…In the realization of self-value, social responsibility also depends on the realization of value. The results of environmental protection are not only conducive to the construction of a green social environment but also can reduce the damage to the ecosystem [21]. However, this kind of green behavior is limited, involving the domain, region, improvement time, and the consciousness of the enterprise itself.…”
Section: Apple's Social Responsibilitymentioning
confidence: 99%